Schmidite and wildenauerite, two new schoonerite-group minerals from the Hagendorf-Süd pegmatite, Oberpfalz, Bavaria. (29th June 2018) - Grey, Ian E.; Keck, Erich; Kampf, Anthony R.; Cashion, John D.; MacRae, Colin M.; Glenn, Alexander M.; Gozukara, Yesim
Abstract: Schmidite, Zn(Fe 3+ 0.5 Mn 2+ 0.5 )2 ZnFe 3+ (PO4 )3 (OH)3 (H2 O)8 and wildenauerite, Zn(Fe 3+ 0.5 Mn 2+ 0.5 )2 Mn 2+ Fe 3+ (PO4 )3 (OH)3 (H2 O)8 are two new oxidised schoonerite-group minerals from the Hagendorf-Süd pegmatite, Hagendorf, Oberpfalz, Bavaria, Germany. Schmidite occurs as radiating sprays of orange–brown to copper-red laths on and near to altered phosphophyllite in a corroded triphylite nodule, whereas wildenauerite forms dense compacts of red laths, terminating Zn-bearing rockbridgeite. The minerals are biaxial (+) with α = 1.642(2), β = 1.680(1), γ = 1.735(2) and 2Vmeas = 81.4(8)° for schmidite, and with α = 1.659(3), β = 1.687(3), γ = 1.742(3) and 2Vmeas = 73(1)° for wildenauerite. Electron microprobe analyses, with H2 O from thermal analysis and FeO/Fe2 O3 from Mössbauer spectroscopy, gave FeO 0.4, MgO 0.3, Fe2 O3 23.5, MnO 9.0, ZnO 15.5, P2 O5 27.6, H2 O 23.3, total 99.6 wt.% for schmidite, and FeO 0.7, MgO 0.3, Fe2 O3 25.2, MnO 10.7, ZnO 11.5, P2 O5 27.2, H2 O 24.5, total 100.1 wt.% for wildenauerite. The empirical formulae, scaled to 3 P and with OH – adjusted for charge balance are Zn1.47 Mn 2+ 0.98 Mg0.05 Fe 2+ 0.04 Fe 3+ 2.27 (PO4 )3 (OH)2.89 (H2 O)8.54 for schmidite and Zn1.11 Mn 2+ 1.18 Mg0.05 Fe 2+ 0.08 Fe 3+ 2.47 (PO4 )3 (OH)3.25 (H2 O)9.03 for wildenauerite. The two minerals have orthorhombic symmetry, space group Pmab and Z = 4. The unit-cell parameters from refinement of powder X-ray diffraction data are a = 11.059(1), b = 25.452(1) and c = 6.427(1) Å for schmidite, and a = 11.082(1), b = 25.498(2) and c = 6.436(1) Å for wildenauerite. The crystal structures of schmidite and wildenauerite differ from that of schoonerite in having minor partitioning of Zn from the [5] Zn site to an adjacent vacant tetrahedral site [4] Zn, separated by ~1.0 Å from [5] Zn. The two minerals are distinguished by the cation occupancies in the octahedral M 1 to M 3 sites. Schmidite has M 1 = M 2 = (Fe 3+ 0.5 Mn 2+ 0.5 ) and M 3 = Zn and wildenauerite has M 1 = M 2 = (Fe 3+ 0.5 Mn 2+ 0.5 ) and M 3 = Mn 2+ .